8-week additional sensomotoric warm-up drills improves motor performance and postural stability in high-performance female Rugby-7 players - Jaskulskia, K.; Bobowika, P.; Wysoczanskia, B.; Starczewskia, M. (Acta Kinesiologica, 2024)
Purpose: The purpose of this study was to evaluate the effectiveness of a personalized training program to improve lower limb muscle strength and balance in professional female rugby 7 players. Given the strong association between postural stability, muscle strength and injury risk among athletes, and given the high incidence of injuries in rugby, preventive measures are warranted.